Q Fever Serological Survey and Associated Risk Factors in Veterinarians, Southern Belgium, 2013. Issue 3 (8th January 2016) - Dal Pozzo, F.; Martinelle, L.; Léonard, P.; Renaville, B.; Renaville, R.; Thys, C.; Smeets, F.; Czaplicki, G.; Van Esbroeck, M.; Saegerman, C.
Summary: A sero‐epidemiological survey was organized among veterinarians working in Southern Belgium to estimate the seroprevalence of Q fever and the risk factors associated with exposure. A total of 108 veterinarians took part to this cross‐sectional study, with a majority practicing with livestock animals. The overall seroprevalence was 45.4%, but it increased to 58.3% among veterinarians having contact with livestock. Three main serological profiles were detected (relatively recent, past and potentially chronic infections). The contact with manure during the prior month was the risk factor associated with seropositivity after multivariate logistic regression analysis. Classification and regression tree analysis identified the age as the most predictive variable to exclude potentially chronic infection in apparently healthy seropositive veterinarians. In conclusion, livestock veterinarians practicing in Southern Belgium are highly exposed to Q fever, a neglected zoonosis for which serological and medical examinations should be envisaged in at risk groups.